The telecom revolution in India technology, regulation, and policy - Sridhar, Varadharajan (New Delhi ; Oxford : Oxford University Press, 2012)
A comprehensive survey of all segments of the Indian telecommunications sector-basic, mobile, national and long distance telephony, internet, satellite, television, and FM broadcasting services. Discussing network externalities economies of scale and scope, it analyses their effects on market structure and regulation.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Telecommunication -- India; Telecommunication policy -- India